Focal electrical stimulation of human retinal ganglion cells for vision restoration. (1st December 2022) - Madugula, Sasidhar S; Gogliettino, Alex R; Zaidi, Moosa; Aggarwal, Gorish; Kling, Alexandra; Shah, Nishal P; Brown, Jeff B; Vilkhu, Ramandeep; Hays, Madeline R; Nguyen, Huy; Fan, Victoria; Wu, Eric G; et al.
Abstract: Objective . Vision restoration with retinal implants is limited by indiscriminate simultaneous activation of many cells and cell types, which is incompatible with reproducing the neural code of the retina. Recent work has shown that primate retinal ganglion cells (RGCs), which transmit visual information to the brain, can be directly electrically activated with single-cell, single-spike, cell-type precision – however, this possibility has never been tested in the human retina. In this study we aim to characterize, for the first time, direct in situ extracellular electrical stimulation of individual human RGCs. Approach . Extracellular electrical stimulation of individual human RGCs was conducted in three human retinas ex vivo using a custom large-scale, multi-electrode array capable of simultaneous recording and stimulation. Measured activation properties were compared directly to extensive results from macaque. Main results . Precise activation was in many cases possible without activating overlying axon bundles, at low stimulation current levels similar to those used in macaque. The major RGC types could be identified and targeted based on their distinctive electrical signatures. The measured electrical activation properties of RGCs, combined with a dynamic stimulation algorithm, was sufficient to produce an evoked visual signal that was nearly optimal given the constraints of the interface. Significance . These results suggest the possibility of high-fidelity vision restoration in humans using bi-directional epiretinal implants.